Unification of hydrogen-enhanced damage understanding through strain-life experiments for modeling. (July 2019) - Martin, M.L.; Looney, C.; Bradley, P.; Lauria, D.; Amaro, R.; Slifka, A.J.
Highlights: H2 -environment mechanical-test apparatus adapted for fully-reversed strain-life tests. Testing in hydrogen shows a noticeable reduction in strain-life compared to in air. Dislocation density is the same in air and H2 while dislocation distribution changes. Strain-control testing decouples H2 effects on deformation mechanisms. Abstract: Strain-life testing of a 4130 pressure vessel steel was conducted in hydrogen gas through the careful adaptation of an existing hydrogen-gas mechanical-testing apparatus. The strain-life mechanical results reveal that hydrogen has a significant effect on the strain-life, and impacts both the elastic and plastic responses of the material. Microscopy analysis shows a distinct difference in the microstructural development of the material after cyclic loading in air compared to after loading in hydrogen gas. These experimental results will inform coupled damage and deformation modeling.